A reliable in vitro rumen culture system and workflow for screening anti-methanogenic compounds - Philip P. Laric; Armina Mortazavi; Ewa Węgrzyn; Kathrin Simon; Pauline S. Rittel; Florian M. Trefz; Benedikt Sabass (PLoS ONE, 2025)
Arguably the biggest man-made challenge of the century is halting climate change. Livestock’s methane (CH 4 ) emissions, a greenhouse gas with a higher global warming potential than carbon dioxide (CO 2 ), represent a prime target for reducing anthropogenic impact. While the reduction of enteric methane emissions through feed additives has been demonstrated, potent and affordable compounds inhibiting methanogenesis in ruminants are not yet well established. Reliable methods for reproducible cultivation of the rumen microbiome in the laboratory are an essential tool for the study of methanogenesis. We have developed a versatile setup that allows for the cultivation of the ruminal microbiome in a benchtop configuration and combines, miniaturizes, and improves existing systems. The design is based on standard laboratory equipment, including bottles, serological pipettes, tubing, and Luer-Lock valves. The apparatus enables long-term cultivation of primary cultures extracted from the rumen of slaughtered cattle. We describe rumen content acquisition, preparation, the cultivation procedure, and demonstrate the system’s performance. The efficacy of the system is demonstrated through the administration of various concentrations of state-of-the-art methanogenesis inhibitors. These inhibitors include lyophilized Asparagopsis taxiformis (AT), bromoform (BF), iodoform (IF), 3-nitrooxypropanol (3-NOP), rapeseed oil, and BF dissolved in rapeseed oil, with maximum CH 4 reductions of 96.29% (p = 5.00E-05, Cohen’s d = 30.29) , 98.22% (p = 2.88E-05, d = 23.07) , 96.26% (p = 1.03E-05, d = 30.29) , 74.63% (p = 8.88E-05, d = 13.32) , 28.96% (p = 0.001, d = 3.99), and 98.51% (p = 4.18E-06, d = 39.94) , respectively, in comparison to the negative control. The gas production dynamics in our setup align with previously published results, which supports the validity of the system. Compared to conventional methodologies, the described setup offers enhanced versatility and ease of use. Furthermore, Fourier-transform-infrared-spectroscopy is implemented in a novel and low-cost approach for quantifying CH₄ and CO₂ in the headspace gas. Together, these methodological advances provide an accessible and reproducible platform for long-term in vitro rumen cultivation for the screening of anti-methanogenic additives.